Duas novas espécies e gêneros de Eriococcidae (Hemiptera) indutores de galhas em Malvaceae e Anacardiaceae neotropicais (Lundiana: International Journal of Biodiversity, 2011)
This paper describes two new genera and species of gall-inducing Eriococcidae from the Neotropics: Eriogallococcus isaias Hodgson & Magalhães gen. & sp. nov. from Brazil, which forms tall conical galls on the leaflets of Pseudobombax grandiflorum (Malvaceae), and Dromedaricoccus hansoni Hodgson & Miller gen. & sp. nov. from Costa Rica, in bulbous swellings on the young stems, petioles and underside of the mid-veins of leaflets of Astronium graveolens (Anacardiaceae). The adult female, adult male, pupa, 2ndinstar male and crawler of E. isaias are described and illustrated but only the adult female and adult male of D. hansoni are described and illustrated. Keys are provided for the identification of (i) all eriococcid genera now known from the Neotropics as recognised by Hodgson & Miller (2010) based on the morphology of the adult female and (ii) all Neotropical genera based on adult males for which this stage is known.